2013
DOI: 10.1177/1074248413503044
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Protects Mice From Coxsackievirus B3-Induced Myocarditis by Inhibiting the Phosphatidylinositol 3 kinase/Akt/Nuclear Factor-κB Pathway

Abstract: Viral myocarditis is an inflammation of the myocardium, and coxsackievirus B3 (CVB3) is one of the most important etiologic agents. Curcumin is an active ingredient of Curcumin longa, which has been used as a traditional Chinese herb for the treatment of various inflammatory diseases. The aim of this study was to explore the therapeutic effect of curcumin on CVB3-induced myocarditis and the underlying mechanism. Our results showed that treatment with curcumin could significantly attenuate CVB3-induced myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 40 publications
1
20
0
2
Order By: Relevance
“…Moreover, a systemic and myocardial reduction in these cytokines, and ultimately NF-κ-β, was also seen following administration of curcumin in Coxsackievirus-infected mice (Song et al. 2013 ). Although we did not analyze the NF-κ-B pathway in this study, we think that the biological effects of curcumin could be due to the inhibition of this transcription factor during the inflammatory process.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a systemic and myocardial reduction in these cytokines, and ultimately NF-κ-β, was also seen following administration of curcumin in Coxsackievirus-infected mice (Song et al. 2013 ). Although we did not analyze the NF-κ-B pathway in this study, we think that the biological effects of curcumin could be due to the inhibition of this transcription factor during the inflammatory process.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, CMN showed noticeable resistance to cardiac hypertrophy caused by banding of the aorta, and the progression of heart failure was decreased by NF-κB activation and monocyte chemoattractant protein-1 (MCP-1), IL-6, IL-1β, and TNF-α mRNA and protein expression induced by aortic banding ( 37 ). Also, Song et al ( 38 ) demonstrated that CMN reduces the systemic and local expressions of NF-κB, IL-6, and IL-1β in the myocardium as evidenced by ameliorated symptoms of myocarditis. In a different study by Wang et al ( 39 ), CMN downregulated the levels of proinflammatory cytokines in the ischemic heart, which is concomitant with reduced TNF-α and IL-6 levels, infarct size, and ameliorated ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis response is an important pathophysiological change in the early stage of myocardial I/R that further leads to severe heart failure . Apoptosis, necrosis, and autophagic cell death are possibly the final arbiters of cardiomyocyte numbers following AMI; cell apoptosis may be associated with a variety of damaging stimuli, particularly continuous I/R . Therefore, the inhibition of cardiomyocyte apoptosis is particularly important for reducing myocardial I/R damage.…”
Section: Discussionmentioning
confidence: 99%